The influence of independence and compensation of the directors on family firms and real earnings management - Adeeb Abdulwahab Alhebri; Shaker Dahan Al-Duais; Amal Mohammed Almasawa (Cogent Economics & Finance, 2021)
This study investigates real earnings management in family firms and further examines the moderating effects of the independence and compensation of directors. Based on a sample of 106 non-financial public listed firms over 5 years in Saudi Arabia, the empirical results show that family firms are positively linked to real earnings management. This result supports the entrenchment hypothesis that family firms have lower earnings quality due to manipulation in real activities. Further, we found evidence that the proportion of independent directors and the compensation paid to directors both interacted in family firms to reduce real earnings management. Our findings suggest that increasing the proportion of independent directors and paying higher compensation to directors are one workable way for family firms to mitigate their real earnings management behaviour.
Keywords: 330; director's compensation; directors' independence; family firms; real earnings management